(untitled) (Scientia Agropecuaria, 2021)
Nano fertilizers offer benefits in nutrition management through their strong potential to increase nutrient use efficiency. Traditional fertilizers are not only costly for the producer but may be harmful to humans and the environment. Furthermore, nano fertilizers may also be used for enhancing abiotic stress tolerance. This study was performed on the evaluation of nano chelated nitrogen and urea fertilizers on the physiological characteristics of wheat under drought stress conditions. Experiments were carried out in two locations in Fars province, Iran. The experimental design was performed as a split-split plot in RCBD design. The first factor included irrigation treatments (normal and withholding irrigation at the flowering stage), sub factor was nitrogen treatment (0, 37, 74 and 110 k g.ha-1) in the form of Urea fertilizer, and sub-sub factor was nitrogen (0, 14, 27 and 41 kg.ha-1) in the form of nano chelated nitrogen fertilizer. Studied traits were RWC, Ion Leakage, Protein, Phosphorus and Potassium content, Remobilization and photosynthesis rate. According to the analysis of variances, stress, nitrogen (urea) and nano chelated nitrogen had significant effects on all studied traits. Mean comparisons showed that drought stress led to 13% reduction in RWC, 21% Ion Leakage, 26% Protein, 13% Phosphorus and 26% Potassium content, 22% Remobilization and 69% photosynthesis rate compared to normal irrigation. In conclusion Application of 41 kg.ha-1 nano chelated nitrogen fertilizer in comparison with urea led to increase 4% in Rwc, 3% Ion leakage, 52% protein, 26% phosphor, 6% potassium, 6% Remobilization and 21% photosynthesis rate compared to control, respectively.